Responses to VCT for HIV among young people in Kampala, Uganda - Råssjö, Eva-Britta; Darj, Elisabeth; Konde-Lule, Joseph; Olsson, Pia (African Journal of AIDS Research, 2007)
Attitudes to voluntary counselling and testing (VCT) for HIV among young men and women in a slum area of Kampala, Uganda, were studied through 22 individual semi-structured interviews and 5 focus group discussions. Attitudes to VCT ranged from having no problem with the procedure to being very reluctant. Despite fear of stigma, the participants perceived 'positive living' after HIV testing as realistic. VCT was regarded as an important step to avoid HIV infection, but informants expressed the need for the service to be more accessible in terms of cost, time and quality of pre- and post-test counselling. We argue that counselling without HIV testing should be available for those who are reluctant to test. Poverty and gender power imbalances appeared to limit youths' possibility of making rational decisions about sexual behaviour and accessing VCT. The importance of considering the context in which such issues are being negotiated and decided is highlighted.
Keywords: Youth services; Sex differentials; Attitudes